PERGANTIAN POPULASI BAKTERI HETEROTROF, ALGAE DAN PROTOZOA DI LAGOON BTDC UNIT PENANGANAN LIMBAH NUSA DUA BALI - Susun Parwanayoni, Ni Made (Bumi Lestari; Vol 8 No 2 (2008))
This research was carried out at Nusa Dua Lagoon, Nusa Dua – Bali in the year of 2006. The research was aimed to find out the concentration of heterotrophic bacteria, algae and protozoa, as well as to observe the change of the population in the lagoon. Results of this study showed that the highest concentration of the population of heterotrophic bacteria was on pond 4b (aerated pond 2), algae population was highest at pond 5a (sedimentation pond 1), and the population of protozoa was highest on pond 5b (sedimentation pond 2). The population of heterotrophic bacteria was replaced by algae and then algae was taken over by protozoa.
Keywords: population